POLA YANG DIUSULKAN DALAM MENDUKUNG KEBERLANJUTAN KEWIRAUSAHAAN SOSIAL - Saragih, Rintan; Nadapdap, Kristanty M. N.; Elisabeth, Duma Megaria (Majalah Ilmiah METHODA, 2023)
Social entrepreneurship is currently receiving attention in a number of countries, including Indonesia. The existence of social entrepreneurship can make a real contribution to improving the community's economy. This research was conducted in Deli Serdang district, North Sumatra with informants who were social entrepreneurs. From the initial map, information was obtained that in the absence of a brand, the need for support from an institution and differences in the behavior of social entrepreneurship actors in viewing institutional support. This research uses qualitative research with a phenomenological approach. The research results show a number of categories, memo fund themes which then produce patterns in supporting the desire for social entrepreneurial activities.